Unraveling the Essence of Crime in International Criminal Law: A Review of Iryna Marchuk’s Work - Amandha, Asyaffa Ridzqi (Universitas Negeri Semarang, 2023)
This review encapsulates the essence of Iryna Marchuk's seminal work,